Peran Dinas Sosial dan Pemberdayaan Masyarakat dalam Menangani Pengemis di Kota Gorontalo - Lucyane Djaafar; Sastro Wantu; Roni Lukum; Saleh Al Hamid (Ideas: Jurnal Pendidikan, Sosial dan Budaya, 2022)
Poverty is a condition of a person who is not able to meet the needs of his life. Many factors cause someone to decide to take up the profession as a beggar, namely economic factors, education, and environmental factors. The purpose of this study was to find out how the role of social services and community empowerment in dealing with beggars in Gorontalo City. The method used in this research is a qualitative approach with a case study method to obtain results and data analysis. The results showed that the role of social services and community empowerment in dealing with beggars in Gorontalo City was carried out through coaching with mental guidance, empowerment by providing training and financing by providing capital to beggars to run businesses.